CALL-EJ on-line - JALT CALL SIG.; Japan Association for Language Teaching (Japan : CALL-EJ On-line, 1999)
A collaborative referred journal formerly CALL -EJ in Japan and On-CALL in Australia. Includes articles on the research and practice in CAI (Computer assisted instruction), CMI (Computer managed instruction) , CALT (Computer assisted language teaching), CALL (Computer assisted language learning), CELL (Computer enhanced language learning) in ESL, EFL, JSL, JFL or other languages.
'CALL-EJ on-line is part of the JALT CALL SIG family.'
Title from title screen (viewed on Mar. 31, 2005).
Text.
Mode of access: Internet and World Wide Web. Available at: http://www.tell.is.ritsumei.ac.jp/callejonline/index.php
Formed by the union of CALL-EJ and On-CALL.
Selected for archiving
Keywords: Language and languages -- Computer-assisted instruction -- Periodicals